Prähabilitation abseits spezialisierter Zentren: Ist Prähabilitation auch auf dem Land machbar? - Seyfried, Steffen; Reißfelder, Christoph; Hardt, Julia (Die Chirurgie, 2025)
Prehabilitation is becoming increasingly more important as an integral component of perioperative management. It improves the functional reserves before surgical interventions and reduces postoperative complications. While specialized centers have successfully implemented prehabilitation programs, the comprehensive implementation especially in rural areas remains challenging. Organizational, infrastructural and financial barriers exacerbate the adaptation outside university facilities; however, hybrid and digital approaches offer promising solutions for decentralized care. A sustainable integration into the healthcare system requires interdisciplinary collaboration, political support and adapted reimbursement structures.